PaleoMaps: SDI for open paleoenvironmental GIS data - Willmes, Christian; Bolten, Andreas; Bubenzer, Olaf; Bareth, Georg (International journal of spatial data infrastructures research, 2017)
Paleoenvironmental studies and corresponding data are abundantly published and available in scientific records. However, paleoenvironmental data sets are comparatively rarely provided in GIS data formats. Here, we present an Open Science approach for collecting and creating GIS data, visualizing it in maps of paleoenvironments, and publishing them in a web-based Spatial Data Infrastructure (SDI), for access by the archaeology and paleoenvironment communities. The Open Science approach to the publication of data allows to properly cite the published data sets as bibliographic sources in research that builds upon these data sets. This paper has its focus on the implementation and setup of the Free and Open Source Software for Geospatial (FOSS4G)-based SDI, and on the workflow for compiling and publishing the GIS data